High le fort I surgically assisted rapid maxillary expansionOrtodonti Anabilim Dalı - Dzulkhaini, Anas (My University, 2012)
Yüksek Le Fort I Kortikotomi İle Gerçekleştirilmiş Hızlı Maksiler Genişletmenin Çalışmanın amacı, yüksek Le Fort I kortikotomi ile gerçekleştirilmiş hızlı maksiler genişletmenin (SARME) etkilerini belirlemektir. Yüksek Le Fort I kesinin sebebi özellikle malar bölge yumuşak doku profilinin iyileştirilmesidir. Çalışmada, Marmara Üniversitesi Dişhekimliği Fakültesi Ortodonti vurmuş 6 hasta yer almıştır. Örnekler, iskeletsel olarak erişkin, ortalama yaşları 18.15 ± 0.96 olan daha önce ortodontik tedavi görmemiş bireylerdir. Hasta seçim kriterleri, hiçbir tıbbi sorunun bulunmaması, orta yüz bölgesinde hipoplazi, dar maksilla ve posterior çapraz kapanış mevcudiyeti olarak belirlenmiştir. Akrilik splintle gerçekleştirilmiş SARME, maksiler transversal ilişkinin düzeltilmesi için uygulanan başlangıç tedavi planın bir parçasıdır. Kortikotomi hattındaki modifikasyon orta yüz bölgesindeki yetersizliğin düzeltilmesi amacıyla yapılmıştır. Kayıtlar ekspansiyon öncesi ve ekspansiyondan 6 ay sonra alınmıştır. Kayıtlar 3D bilgisayarlı tomografi, ağız içi ve dışı fotoğraflar ve ortodontik modellerden oluşmaktadır. Tomografiler Mimics 10.11 ve Simplant Pro 13.0 programlarıyla analiz edilmiştir. Verilerinin incelenmesinden sonra paranazal bölgede 3-4 mm’lik ilerleme bulunmuştur. Daha az miktarda genişletmeyle transvers ve sagital olarak gelişme gözlemlenmiştir. Ekspansiyon ve malar bölgedeki gelişmeler birbiriyle ilişkili bulunmuştur, fakat bu ilişki klinik olarak anlamlı değildir. Anahtar kelimler: High Le Fort I, Surgically Assisted Rapid Maxillary Expansion

The aim of this study is to determine the effects of Surgically Assisted Rapid Maxillary Expansion (SARME), following high Le Fort I corticotomy. The objective of a high Le Fort I cutting line is solely in the interest of improving patients soft tissue profile specifically the malar region. The study involved a group of 6 selected patients who were attending the Department of Orthodontics of the Dental faculty of Marmara University, Istanbul for orthodontic treatment. Samples were skeletally matured adults with a mean age of 18.15 ± 0.96 years with no previous orthodontic treatment. Criterias for patient selection were no underlying medical disorder, midfacial hypoplasia, narrow maxilla and posterior crossbites. SARME with hyrax cap-splint is part of initial treatment plan for correcting the maxillary transverse discrepancy. Modification in the corticotomy line were performed primarily to improve the soft tissue profile as midfacial deficiency is present. Records were taken before and 6 months post-expansion. Record included were 3-D computed tomography, intra-oral and extra-oral photographs and orthodontic models. Tomograms were analyzed by Mimics 10.11 computer software and Simplant Pro 13.0. After examining the data, 3-4 mm of forward movement of the paranasal region was found. Positive changes in the malar region were observed transverse and sagittally among patients with lower amount of expansion. There is a correlation between expansion of the maxilla and changes in the malar. However, the values were clinically insignificant. Key words: High Le Fort I, Surgically Assisted Rapid Maxillary Expansion
Keywords: Ağız ve Diş Sağlığı; Ortodonti; Tıp